Mechanical-Chemical Activation of Coal Fly Ashes: An Effective Way for Recycling and Make Cementitious Materials - Fernández-Jiménez, Ana; Garcia-Lodeiro, Ines; Maltseva, Olga; Palomo, Angel (Frontiers in Materials, 2019)
This paper is wholly committed to resource efficiency through the valorisation of waste from other industries, and more specifically fly ash as a raw material to produce concrete-like geopolymers. In particular, this study aimed to determine the effect of the physical and chemical characteristics of recycled coal fly ash used to manufacture alkaline cement on reaction kinetics and product microstructure and performance. The ash was mixed with 8 M NaOH and cured for 20 h at 85oC and RH of 90 % to form a compact paste, after which mechanical strength was determined and the reaction rate was calculated using isothermal conduction calorimetry. The findings showed that vitreous content, (SiO2/Al2O3)reactive and (especially) particle size distribution play a very important role in both the development of cement mechanical strength and the composition and structure of the reaction products formed.